DAMPAK PARKIR LIAR DI PERUMAHAN TERHADAP MASYARAKAT SETEMPAT GARDEN CITY RESIDENCE - Pandapotan H., Alberto (JMTS: Jurnal Mitra Teknik Sipil, 2023)
Currently, illegal parking for housing is increasingly seen in residential areas which affected various aspects of life.. At present, the legal basis for illegal parking in residential areas is getting tighterHowever, there are still many people who are unaware about housing parking regulations. Therefore, the public's perception of illegal parking in housing still should be studied further. The aim of this study is to determine the public perception perception of the impact of illegal parking in housing on the local community. The method used was an online survey of 150 respondents who were residents of one of the settlements where the research was conducted.